Beyond Studies Tarekat Rifa’iyah Kalisalak: Doktrin, Jalan Dakwah, dan Perlawanan Sosial - Kaprabowo, Andi (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2019)
This article tries to exploring the substance of the Rifa’iyah tarekat movement which is the subject of public discussion. This study was examined using a qualitative method by tracing the history of the biography of Haji Rifa'i as the founder of the tarekat. This study succeeded in finding the existence of the Rifa'iyah order as a group that consistently opposed the hegemony of the government and the Dutch colonial. Evidence of consistency has been unraveled by traces of the historical alignment of religious movements. This trace is proven by the teachings of the tarekat which are very doctrinal to their followers. So far, the existence of the Rifa'iyah tarekat tends to be deviant but the reality of the teachings is able to provide lessons about peaceful invitation and methods of social resistance that are an inseparable part of the process of spreading Islam. Doctrine, preaching and social resistance are three existences that are still alive in society. This existence as a discursive narrative that is intimately connected with the study of social movements. Although the existence of the Rifa'iyah tarekat movement invited various debates that led to the attack of a group of times and actions to silence the existence of the tarekat by the government.Artikel ini mencoba menelusuri hakekat gerakan tarekat Rifa’iyah yang menjadi perbincangan masyarakat. Penelitian ini dikaji menggunakan metode kualitatif dengan penelusuran sejarah biografi Haji Rifa’i sebagai pendiri tarekat. Kajian ini berhasil menemukan keberadaan tarekat Rifa’iyah sebagai kelompok yang konsisten menentang hegemoni pemerintah dan kolonial Belanda. Bukti konsistensi tersebut telah terurai dengan jejak pelurusan sejarah gerakan keagamaan. Jejak ini terbukti dengan ajaran tarekat yang sangat doktriner kepada para pengikutnya. Selama ini, eksistensi tarekat Rifa’iyah cenderung dianggap menyimpang namun realitas ajarannya mampu memberikan pelajaran tentang dakwah yang damai dan metode perlawanan sosial yang menjadi bagian tidak terpisah dari proses penyebaran Islam. Doktrin, jalan dakwah, dan perlawanan sosial merupakan tiga eksistensi yang masih hidup di masyarakat. Eksistensi ini sebagai narasi diskursif yang berkawan erat dengan studi gerakan sosial. Walaupun eksistensi gerakan tarekat Rifa’iyah mengundang beragam perdebatan yang berujung kepada penyerangan sekelompok masa dan tindakan membungkam keberadaan tarekat oleh pemerintah.